Kontribusi Computer Anxiety dan Motivasi Terhadap Literasi Teknologi Siswa SMA Negeri 8 Kota Serang - Popi Dayurni; Umalihayati Umalihayati (Universitas Lampung, 2023)
One of the capabilities expected in 21st century education is technological literacy. Technological literacy is the ability to use and utilize technology, especially for learning. However, based on observations made, there are still many students who have low technological literacy. Factors that influence technological literacy are computer anxiety and motivation. The purpose of this study is to explain how much computer anxiety and motivation contribute to students' technological literacy abilities. This study uses a type of correlational quantitative research. This research was conducted at Serang City Public High School where previously researchers conducted instrument trials and then researchers conducted research through questionnaires and tests on 328 students. To test the hypothesis in this study used regression analysis techniques, correlation analysis, and F test analysis. Based on the results of the study, it was found that the data was normal, linear and there was no multicollinearity. The test results obtained rx1y value of 0.629 with rtable 0.1088 because rcount rtable, the first hypothesis was accepted. Then the rx2y value is 0.565 because rcount rtable, the second hypothesis is accepted. And it is supported by the value of Fcount = 146.384 and Ftable = 2.632 so that Fcount Ftable (146.38 2.632). With a significant correlation, it can be concluded that computer anxiety and motivation together make a positive contribution to the technological literacy skills of students at SMA Negeri 8 Kota Serang by 57.5%. Kata kunci: Computer Anxiety, Literasi Teknologi, Motivasi, Pendidikan abad 21